2021
DOI: 10.3390/ijerph18042150
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Prehospital Stroke Care and Stroke Mimic Patterns during the COVID-19 Lockdown

Abstract: The impact of COVID-19 lockdown on prehospital stroke care is largely unknown. We aimed to compare stroke care patterns before and during a state-wide lockdown. Thus, we analysed prospective data of stroke alerts referred to our stroke centre between 1 December 2019 and 16 June 2020, and compared them between two periods—15 weeks before and 13 weeks during the state-wide lockdown declared in Lithuania on 16 March 2020. Among 719 referrals for suspected stroke, there was a decrease in stroke alerts (rate ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 33 publications
3
25
0
Order By: Relevance
“…It may be attributable to the preservation of access to reperfusion therapy in the home quarantine period. This finding is in line with other centers [13] , [19] , [20] , whereas in apparent conflict with the study conducted by Briard et al [21] . In an observational cohort study, longer door-to-needle and door-to-recanalization metrics were demonstrated during the COVID-19 pandemic, partly attributed to the institution of infection control measures [21] .…”
Section: Discussionsupporting
confidence: 55%
“…It may be attributable to the preservation of access to reperfusion therapy in the home quarantine period. This finding is in line with other centers [13] , [19] , [20] , whereas in apparent conflict with the study conducted by Briard et al [21] . In an observational cohort study, longer door-to-needle and door-to-recanalization metrics were demonstrated during the COVID-19 pandemic, partly attributed to the institution of infection control measures [21] .…”
Section: Discussionsupporting
confidence: 55%
“…Most studies compared the pandemic period (ranging from January to June 2020) to a similar period in the preceding year (range January to June 2019) [28][29][30][31]33,35,39,[41][42][43]45,46,[48][49][50]52,[54][55][56][57][58]60 or the months preceding the pandemic (range September 2019 to December 2019). 8,32,34,[36][37][38]40,44,47,51,53,59,[61][62][63]…”
Section: Resultsmentioning
confidence: 99%
“…The onset-to-door time was reported in 14/37 studies. 29,30,44,46,48,49,52,54,55,[57][58][59]61,63 There was no difference in mean onset-to-door time during pandemic when compared to pre-pandemic period (standardized mean difference=-0.2; 95% CI, -0.8 to 0.3).…”
Section: Time From Onset To Admissionmentioning
confidence: 99%
“…This may be the result of public concern and the diversion of emergency department (ED) resources to COVID-19 patients. A prospective study in an academic stroke centre with a significant urban catchment population conducted during the COVID-19 lockdown in Vilnius, Lithuania, similarly found a decreased rate of stroke alerts and admissions, as well as a decrease in prehospital stroke triage quality and significant hospital arrival delays from symptom onset, but the timeliness of stroke care delivery in the ED was not negatively affected by the lockdown [ 7 ]. It is difficult to ascertain the exact reasons behind the successful preservation of in-hospital stroke care goals during the COVID-19 pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…Advanced neuroimaging has a particularly important implication during the pandemic. Possible treatment delays due to the current crisis related to increased time intervals “onset to door” and/or “door to needle”; therefore, selection of patients for mechanical thrombectomy poses new challenges and requires refinement of established protocols [ 3 , 6 , 7 ]. Although minimising time to treatment is critical, the decision to perform mechanical thrombectomy should be individualised because current data shows that the association between endovascular reperfusion and improved functional outcome is not strictly time dependent [ 28 , 50 ].…”
Section: Resultsmentioning
confidence: 99%